Szkolenie i doskonalenie personelu jako komponent zarządzania jakością w niepublicznych zakładach ochrony zdrowia - Jankowiak, Ryszard (Staff Training as a Component of Quality Management in Public Health Centres, 2008)
A modern company needs to employ new methods and techniques of management to keep up with the changes taking place in the contemporary world. The domain that people are particularly concerned about is the Health System that is why in the days of market economy, a patient has become the centre of all the activities of medical establishments. The Polish Heath System is now facing a dilemma of maintaining the past status quo and biding its time or privatising partly or completely. In order to meet the forever rising expectations of the Polish patients, it is necessary to constantly improve the system of quality management, particularly in the public sector. One of the components that secures effective functioning of that system is staff training, where all the employees as well as chief executives undergo the training. The processes and procedures of the training sessions must be planned and performed routinely. To conduct training, specialists or quality management executives are commissioned. Each training guarantees that the workers consciously and collectively participate in achieving their company's aims. The main objective of staff training is to efficiently prepare employees to carry out their professional duties according to the procedures and regulations. The trained staff will also receive guidelines for the running of quality system documents and external audits which will lead to heightened customer satisfaction. Each training should be evaluated in terms of its effectiveness. Evaluation is based on audits and satisfaction surveys conducted among the employees and, above all, patients. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 539-549